Identifying and measuring the severity of somatic symptom disorder using the Self-reported Somatic Symptom Scale-China (SSS-CN): a research protocol for a diagnostic study - Meng Jiang; Weituo Zhang; Xuan Su; Chuang Gao; Bingxu Chen; Zehao Feng; Jialiang Mao; Jun Pu (BMJ Open)
Introduction The detection rate of somatic symptom disorder (SSD) in general hospitals is unsatisfactory. Self-report questionnaires that assess both somatic symptoms and psychological characteristics will improve the process of screening for SSD. The Somatic Symptom Scale-China (SSS-CN) questionnaire has been developed to meet this urgent clinical demand. The aim of this research is to validate the self-reported SSS-CN as a timely and practical instrument that can be used to identify SSD and to assess the severity of this disorder.Methods and analysis At least 852 patients without organic disease but presenting physical discomfort will be recruited at a general hospital. Each patient will undergo a Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5)-guided physician diagnosis, including disease identification and severity assessment, as the reference standard. This research will compare the diagnostic performance of the SSS-CN for SSD, the Patient Health Questionnaire-15 (PHQ-15) and other SSD-related questionnaires. Statistical tests to measure the area under the curve (AUC) and volume under the surface of the receiver operating curve will be used to assess the accuracy of the SSD identification and the severity assessment, respectively. In addition to this standard diagnostic study, we will conduct follow-up investigations to explore the effectiveness of the SSS-CN in monitoring treatment effects.Ethics and dissemination Ethical approval was obtained from the Renji Hospital Human Research Ethics Committee, approval number 2 015 016. The findings of this study will be disseminated via peer-reviewed journals and presented at international conferences.Trial registration number NCT03513185.